Household financial literacy: A literature analysis and review - LinXi Shi; Thien Sang Lim (Atlantis press, 2023)
With the continuous improvement of the financial market system and the increasing abundance of financial services, household financial literacy is increasingly important for optimizing household financial behavioral decisions and enhancing household financial well-being. In order to grasp the research progress and main content of household financial literacy, using 1,144 documents included in the "Web of Science" database from 2003 to the present (up to June 30, 2023) as the basis and CiteSpace software as the data analysis and processing tool, this study demonstrated the research field of household financial literacy through the keyword co-occurrence map and keyword clustering map of the Main topics. On the basis of further combing related literature, the study clarified the concepts, measurement methods, and influencing factors of financial literacy, as well as the role of financial literacy in influencing the financial decision-making behaviors of households in areas such as investment, credit, and entrepreneurship. Finally, it summarized and looked forward to the development of household financial literacy research.